2012
DOI: 10.1371/journal.pone.0044517
|View full text |Cite
|
Sign up to set email alerts
|

Health Assessment and Seroepidemiologic Survey of Potential Pathogens in Wild Antillean Manatees (Trichechus manatus manatus)

Abstract: The Antillean manatee (Trichechus manatus manatus), a subspecies of the West Indian manatee, inhabits fresh, brackish, and warm coastal waters distributed along the eastern border of Central America, the northern coast of South America, and throughout the Wider Caribbean Region. Threatened primarily by human encroachment, poaching, and habitat degradation, Antillean manatees are listed as endangered by the International Union for the Conservation of Nature. The impact of disease on population viability remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 73 publications
5
29
1
Order By: Relevance
“…Lounsbury et al (2001) documented serovars canicola, icterohemorragiae, autumnalis, pyrogenes, hardjo, and pomona from Florida and the Gulf of Mexico. Aragó n-Martínez (2008) and Sulzner et al (2012) found canicola and icterohemorragiae in Antillean manatees and Mathews et al (2012) found icterohemorragiae in Amazonian manatees. Serovars pomona, hardjo, and bratislava have been associated with bovine, porcine, and equine livestock (Khairani-Bejo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lounsbury et al (2001) documented serovars canicola, icterohemorragiae, autumnalis, pyrogenes, hardjo, and pomona from Florida and the Gulf of Mexico. Aragó n-Martínez (2008) and Sulzner et al (2012) found canicola and icterohemorragiae in Antillean manatees and Mathews et al (2012) found icterohemorragiae in Amazonian manatees. Serovars pomona, hardjo, and bratislava have been associated with bovine, porcine, and equine livestock (Khairani-Bejo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other regions, prevalence was lower than in our study. These include Florida (25%), Belize (23%), and Caribbean coasts of Mexico (14.3%; Lounsbury et al 2001;Sanvicente 2005;Sulzner et al 2012; Table 2). For the Amazonian manatee, reported prevalence was 17.3% (Mathews et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Little is known of the causes of death or the prevalence of zoonotic organisms in manatees from Peru; however, Leptospira spp. have been reported to cause mortalities in marine mammals (Visser et al, 1991;Higgins, 2000;Mackereth et al, 2005;Bossart et al, 2012;Sulzner et al, 2012).…”
mentioning
confidence: 99%